Living in Two Worlds: Multi-Locational Household Arrangements among Migrant Workers in China - Schmidt-Kallert, Einhard; Franke, Peter (DIE ERDE – Journal of the Geographical Society of Berlin, 2012)
In the past, the concept of multi-locality has hardly been applied to the study of livelihood strategies of migrant workers in China. The authors of this article present the findings of a research project in five selected rural-urban migration corridors in different parts of China. On the basis of qualitative interviews at both ends of the multi-locational households’ activity spaces, they were able to establish economic reciprocity, strategies for caring and the transfer of knowledge, values and beliefs at the household level. The multi-locational households – defined as units of joint planning – were found to be firmly embedded in informal social networks.